2014
DOI: 10.1117/12.2056813
|View full text |Cite
|
Sign up to set email alerts
|

ART-XC/SRG: status of the x-ray optics development

Abstract: The Astronomical Roentgen Telescope (ART) instrument is a hard-x-ray instrument with energy response up to 30 keV that is to be launched on board of the Spectrum Roentgen Gamma (SRG) Mission. The instrument consists of seven identical mirror modules coupled with seven CdTe strip focal-plane detectors. The mirror modules are being developed at the Marshall Space Flight Center (MSFC.) Each module has ~65 sq. cm effective area and an on-axis angular resolution of 30 arcseconds half power diameter (HPD) at 8 keV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Telescope ART-XC is being developed in Space Research Institute of Russian Academy of Sciences in Moscow (IKI RAS) and All-Russian Scientific Research Institute for Experimental Physics (VNIIEF) in the Sarov city. ART-XC mirror systems are being manufactured in MSFC/NASA [4]. ART-XC will increase observatory sensitivity in hard energy band.…”
Section: Object Of the Test And Testing Problem Statementmentioning
confidence: 99%
“…Telescope ART-XC is being developed in Space Research Institute of Russian Academy of Sciences in Moscow (IKI RAS) and All-Russian Scientific Research Institute for Experimental Physics (VNIIEF) in the Sarov city. ART-XC mirror systems are being manufactured in MSFC/NASA [4]. ART-XC will increase observatory sensitivity in hard energy band.…”
Section: Object Of the Test And Testing Problem Statementmentioning
confidence: 99%
“…Four flight modules were produced under an International Reimbursable Agreement between NASA and the Space Research Institute (IKI) in Moscow, Russia, and three flight modules and one spare unit were fabricated under a Cooperative Agreement between NASA and IKI. The details of the mirror design and development can be found in [3,4,5]. Each module consists of 28 concentrically nested (two-reflection) grazing-incidence mirrors made of an electroformed nickel-cobalt alloy and mounted on a single spider through combs glued onto the spider legs.…”
Section: Art-xc Mirror Modulesmentioning
confidence: 99%
“…A number of angular resolution measurements were performed to determine the optimal angular resolution across the FOV. It was found that defocusing a module by intra-focal 7 mm provides more uniform angular resolution across the FOV compared to the resolution at the nominal focal distance [5]. In the following, we adopt each ART-XC module being defocused by 7 mm as a default ART-XC design, unless otherwise stated.…”
Section: Art-xc Mirror Modulesmentioning
confidence: 99%
“…Over the past decade, NASA's MSFC has been improving the angular resolution of hard X-ray (HXR) optics to the point that they now routinely manufacture <26 HPD optics modules for flight payloads (Ramsey et al, 2013;Gubarev et al, 2014). Included in this HXR optics program are mirror modules produced for the ART-XC experiment to be flown on the Spectrum-Roengen Gamma mission (∼25 HPD) system performance up to ∼30 keV and the flight-proven HXR mirrors flown on the HERO and HEROES balloon-bone HXR telescopes.…”
Section: Heroes Opticsmentioning
confidence: 99%
“…(Elsner et al, 2000)), HERO (Ramsey et al, 2002), FOXSI, potential wide-field applications (e.g. Elsner et al, 2011)), and most recently ART-XC (Gubarev et al, 2014).…”
Section: Effective Areamentioning
confidence: 99%